THE EFFECTIVENESS OF ROUND ROBIN (Collaborative Learning Techniques) TO TEACH SPEAKING VIEWED FROM STUDENTS MOTIVATION (An Experimental Research at the first semester Student of UNUGHA CILACAP in the Academic year 2023/2024) - Erina Hastuti (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
The objectives of the research are: (1) to identify whether Round Robin is more effective than Classroom technique in teaching speaking for the first semester Student of UNUGHA CILACAP in the Academic Year of 2023/2024; (2) to identify whether the students having high motivation have better achievement score than those having low motivation to the first semester Student of UNUGHA CILACAP in the Academic Year of 2023/2024 and (3) to identify whether there is an interaction between the teaching techniques and students’ motivation to teach English. The research methodology was experimental. The research was conducted at UNUGHA CILACAP from September 2023 to October 2023. The population of this research was the first semester students of English 1 and the first semester students of English 2. Each of them consists of 40 students. The first semester students of English 1 were as experimental class who were taught using Round robin and the first semester students of English 2 were as control class who were taught using classroom technique. The data were in the form of quantitative data and they were taken from a test. They were the scores of students’ speaking test after having eight times treatment for each class. The researcher analyzed the data using ANOVA or analysis of variance and Tukey test. The data analysis shows the following findings; (1) Round Robin is more effective than classroom method to teach speaking in speaking for the first semester Student of UNUGHA CILACAP in the Academic Year of 2023/2024; (2) The Achievement Score of the students having high motivation is better than that of those having low motivation; and (3) These is an interaction between teaching techniques and students’ motivation. It means that the effectiveness of the teaching technique depends on the level of the students’ motivation while in this case based on the turkey test the students with lower motivation will end up to be taught by using round robin or classroom technique to the first semester Student of UNUGHA Cilacap in the Academic Year of 2023/2024.